Pengaruh Penyuluhan dengan Media Audiovisual Terhadap Kepatuhan Perilaku Konsumsi Tablet Besi pada Ibu Hamil di Puskesmas Kenangan Kecamatan Medan Denai Kota Medan Tahun 2024 - Elfrida Br Sidauruk; Parningotan Simanjuntak; Ingka Kristina Pangaribuan; Friza Novita Situmorang (NAJ Nursing Applied Journal, 2025)
Counseling with media is able to arouse and bring pregnant women into an atmosphere of joy and excitement, where there is emotional and mental involvement. The effectiveness of using outreach media is largely determined by the number of senses of reception involved. The more senses are used, the easier it is to understand the delivery of the extension message. This research aims to determine the effect of counseling using audiovisual media on compliance with iron tablet consumption behavior among pregnant women at Kenangan Public Health Center, Medan Denai District, Medan City in 2024. This type of research is research using a quasi-experimental research method (quasi-experiment) with a pretest-posttest design. The population and sample are all pregnant women from TM III Kenangan Health Center, Medan Denai District, Medan City in 2024 in May-June, as many as 32 people using the Purposive Sampling technique using the Chi Square statistical test. It was concluded that counseling using audiovisual media had an influence on compliance with iron tablet consumption behavior among pregnant women at the Kenangan Community Health Center, Medan Denai District, Medan City in 2024